Analysis of Bank Customer Service Strategies in The Pandemic Time of Covid-19 - Asep Sugara; Kaonang; Dedy Kustyono; Chandra Dwinugraha (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This study aims to identify customer service strategies on the value of expectations and service satisfaction that customers receive. The research method used is quantitative, the research sample used is a simple random sampling method, with a size of 100 customers at Bank BRI KCP Taman Palem, West Jakarta. Indonesian. The collected data were analyzed using a Cartesian diagram. The results of the study were able to identify services and the level of customer satisfaction on the quality of company services from the five service measurement tools, the results were distributed into four quadrants, namely: the reliability dimension was in Quadrant I, the responsiveness dimension was in Quadrant II, the assurance dimension was in Quadrant III and empathy, and tangibility is in Quadrant IV. Based on these results, it is recommended that BRI Bank performs refinement and improvement of several current customer service strategies so that the five dimensions of customer service are at coordinate points in quadrant I.